2004
DOI: 10.1103/physrevlett.93.147003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Effect on the Static Antiferromagnetism of the Electron-Doped SuperconductorPr1xLaC

Abstract: Effects of magnetic fields (applied along the c-axis) on static spin correlation were studied for the electron-doped superconductors Pr1−xLaCexCuO4 with x=0.11 (Tc=26 K) and x=0.15 (Tc=16 K) by neutron scattering measurements. In the x=0.11 sample located near the antiferromagnetic(AF) and superconducting phase boundary, the field dependence of both the magnetic intensity at T=3 K and the onset temperature of the magnetic order exhibits a peak at ∼5 T. In contrast, in the overdoped x=0.15 sample a static AF or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
3
26
2
Order By: Relevance
“…15͑a͒ and 15͑e͔͒, consistent with an earlier report on an overdoped PLCCO ͑T c =16 K͒. 48 Note that in this case the peaks at both positions arise mostly from superlattice and ͑Pr, La, Ce͒ 2 O 3 and there are no static AF orders in the sample ͓Figs. 6͑a͒ and 6͑b͔͒.…”
Section: Effect Of a C-axis-aligned Magnetic Field On Sdw And Af Osupporting
confidence: 90%
See 1 more Smart Citation
“…15͑a͒ and 15͑e͔͒, consistent with an earlier report on an overdoped PLCCO ͑T c =16 K͒. 48 Note that in this case the peaks at both positions arise mostly from superlattice and ͑Pr, La, Ce͒ 2 O 3 and there are no static AF orders in the sample ͓Figs. 6͑a͒ and 6͑b͔͒.…”
Section: Effect Of a C-axis-aligned Magnetic Field On Sdw And Af Osupporting
confidence: 90%
“…Electron-doped Pr 1−x LaCe x CuO 4±␦ , where Pr 3+ has a singlet ground state 47 and La is nonmagnetic, is ideal for this purpose. Using single crystals of Pr 1−x LaCe x CuO 4±␦ with x = 0.11 ͑T c =16 K͒ and x = 0.15 ͑T c =26 K͒, Fujita et al 48 found that a c-axis-aligned magnetic field enhances the residual AF order in the x = 0.11 sample at ͑0.5,1.5,0͒ position, but has no effect in the overdoped x = 0.15 sample. The authors conclude that a c-axis field changes both the magnetic intensity and the onset of the Néel ordering temperature T N for the x = 0.11 sample, with the maximum field effect at ϳ5 T. 48 Our approach to this problem has been slightly different from that of Fujita et al 48 Instead of preparing different SC Pr 1−x LaCe x CuO 4±␦ samples as a function of Ce doping, we grew single crystals of PLCCO using a traveling solvent floating zone furnace.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous muon spin relaxation measurements have observed the emergence of field-induced AF order throughout the volume of optimally doped PLCCO (26), neutron diffraction experiments have failed, possibly because of insufficient sample volume, to detect such a signal for optimally and overly doped PLCCO (27,28). Because our PLCCO samples have no observable static AF order above T ϭ 0.6 K (8), we would expect the observed peak at (1/2, 1/2, 0) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fujita et al used neutrons to study the same Pr 1−x LaCe x CuO 4 samples that Kadono et al investigated with µSR [168]. In zero field, weak AF order was detected in the x = 0.11 sample, in contrast to ZF-µSR measurements that found only random magnetism due to small Pr moments [169].…”
Section: La2−xsrxcuo4mentioning
confidence: 99%